The Power of Preferences: Economic Elites and Light Taxation in Mexico - Gabriel Ondetti (Revista Mexicana de Ciencias Políticas y Sociales)
In recent years Mexico has had the lightest tax burden in Latin America. Using qualitative, historical analysis, this paper argues that a crucial cause of this phenomenon is the resistance of an exceptionally politically mobilized economic elite, which has resulted in the defeat or dilution of repeated attempts at reform. The intensity of elite resistance reflects, in turn, a strongly anti-state ideology constructed through conflict with the state, especially during the 1930s. This emphasis on the historical construction of preferences clarifies a central paradox of the literature on Latin American taxation: the fact that a number of authors agree that elite cohesion and political connections are important, but disagree on whether they hinder or facilitate revenue-raising reform.